Conocimiento en normas internacionales de información financiera y el desempeño laboral del personal contable de Corporación Cayman SAC, periodo 2022 - Gonzales Diaz, Nancy Leonida (2023)
Knowledge is an essential and important tool in the growth and development of every person, and even more when we refer to the labor aspect, it contributes to improve the professional performance that workers assume in each of the tasks entrusted, in such a way that it generates a positive performance aimed at increasing the productivity of the company not only for the benefit of itself, but also for all those who have participated in achieving the goals and objectives established. The present investigation is entitled "Knowledge in International Financial Information Standards and Labor Performance of the accounting personnel of Corporación Cayman SAC, period 2022", its objective is to determine the relationship between knowledge and labor performance presented by said workers for the period of study. Likewise, the research was of a quantitative type and a descriptive correlational design. Finally, after having analyzed the collected data, it has been possible to determine a Rho Spearman correlation coefficient of 0.662 and a degree of significance of 0.037, which means that there is a direct relationship between knowledge and job performance.